EMPOWERING DIGITAL CITIZENSHIP: LIBRARIANS' APPROACHES TO CLOSING THE DIGITAL DIVIDE AND SAFEGUARDING DIGITAL MEMORIES - Abdul Rozak; Era Purike; Awaluddin (Adisam Publisher, 2024)
In today's digital landscape, librarians serve as linchpins in advancing digital citizenship through their efforts to bridge the digital divide and preserve digital memories. Librarians employ tailored digital literacy programs, innovative technologies, and strategic partnerships to ensure equitable access to digital resources and foster digital fluency across diverse communities. Their advocacy for policies promoting digital inclusion and stakeholder collaboration further amplifies their impact. Additionally, librarians recognize the significance of safeguarding digital memories and promoting information literacy amid rapid technological advancements. They safeguard valuable digital content for future generations by guiding digital preservation and information management. This abstract underscores the pivotal role of librarians as advocates for digital literacy and custodians of digital heritage, driving endeavors toward a more inclusive and digitally resilient society. In an age dominated by digital technology, librarians play a crucial role in empowering digital citizenship by addressing the digital divide and preserving digital memories. Through tailored digital literacy programs, innovative technologies, and strategic partnerships, librarians ensure equitable access to digital resources and foster digital fluency across diverse populations. Moreover, their advocacy for policies promoting digital inclusion and stakeholder collaboration amplifies their impact. Librarians also recognize the importance of preserving digital memories and promoting information literacy amidst rapid technological evolution. By offering guidance on digital preservation and information management, they protect invaluable digital content for future generations. This abstract highlights librarians' critical role as champions of digital literacy and custodians of digital heritage, driving initiatives toward a more inclusive and digitally resilient society.